Research of the Effects of Pressure Angle on Mesh Characteristic of Involute Cylindrical Gear - Song Bin (Jixie chuandong)
The mesh model for the conventional involute gear pair is developed. Then the mesh characteristic is solved and analyzed. Based on the mesh model and the calculated results,the effects of normal pressure angle on the meshing slip coefficient,tooth root stress,contact pattern,the maximum contact pressure and the variation of the mesh stiffness are investigated. The results show that the increase of the normal pressure angle tends to increase the bending strength,the contact strength and the ability to prevent scuffing when the normal pressure angle is less than 25°. But,when the normal pressure angle is larger than 25°,the above results will change slightly. Also,it will decrease the root stress when the normal pressure angle is less than 25°. However,when the normal pressure angle is larger than 25°,the root stress will become a little larger. The increase of the normal pressure angle also can decrease the contact ratio,improve the contact pattern and decrease the variation of the mesh stiffness. The results of this study can be applied to guide the normal pressure angle selection and design of the involute gear.